PERANAN LEMBAGA PENGEMBANGAN PESISIR MIKRO “MITRA MINA” DALAM UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR DI SUMATERA BARAT - Lucky Zamzami (Asian Journal of Innovation and Entrepreneurship, 2012)
This research focused on the existence of the Institute of Coastal Economic Development Micro Mina Partner " (LEPP M3) was considered quite successful in improving the entrepreneurial culture by forming partnerships"Swamitra Mina". The presence of Partnership "Swamitra Mina" in coastal areas, it will directly reduce the role of moneylenders, so that the partnership of Swamitra Mina can mobilize public funds to be used in fishing activities at sea and fish farming. LEPP-M3 very important role in enhancing the economic welfare of coastal fishingcommunities, especially fishermen working with coastal communities to create self-reliance through the promotion of economic activity, strengthening capital and business development, developing partnerships with cooperatives, other private and government institutions, venture capital fulfillment of coastal communities for more improve their business, expand business activities thereby expanding employment opportunities andstimulate business and increase arousal, which in turn will boost economic growth. Keywords: role, Institute of Coastal Economic Development, The Entrepreneurial Culture Economic Empowerment, fishermen